Domino Aryne Precursor: A Step beyond the Boundary of Traditional Aryne Chemistry - Qiu, Dachuan; Shi, Jiarong; Li, Yang (Synlett, 2015)
In an aim to expand the scope of aryne chemistry with new synthons, a domino aryne precursor bearing an additional ortho-OTf group on Kobayashi reagent is proposed and synthesized. 2,4-Disubstituted benzothiazole could be achieved from benzothioamide derivatives and this reagent with a sequential incorporation of C–S, C–N, and C–C bonds on the consecutive positions of the aryne precursor.
Keywords: aryne; domino aryne chemistry; benzyne; Kobayashi reagent; benzothiazole